Diagnostic efficacy of SEPT9 and PAX5 gene methylation in gastrointestinal cancer and precancerous lesions: SEPT9 and PAX5 methylation in GC - Yan, Zhong; Liu, Hongdao; Wang, Kun (Cellular and Molecular Biology, 2024)
To assess the diagnostic efficacy of SEPT9 along with PAX5 gene methylation detection in gastrointestinal cancer and precancerous lesions, the peripheral blood of 62 patients with gastric cancer (GC) and 60 patients with no evidence of disease (as the control group) were retrospectively collected. The methylation rates of PAX5 and SEPT9 gene promoters in blood samples of GC group were detected by PCR. At the same time, the differences in methylation rates of genes in the two groups were compared, and the predictive value of plasma methylation PAX5 and SEPT9 in GC was evaluated by receiver operating characteristic (ROC) curve. We found that there were 41 cases of methylated PAX5 gene promoter region and 39 cases of methylated SEPT9 gene promoter region in GC group. The control group contained 14 cases of PAX5 gene promoter methylation and 12 cases of RNF¹80 gene promoter methylation. The occurrence of PAX5 promoter methylation was correlated with age of GC patients. There were statistically significant differences in mSEPT9 gene in patients with different TNM stages. Kaplan-Meier survival curve analysis revealed that the three-year overall survival rate of GC patients with PAX5 methylation was lower than that of GC patients without PAX5 methylation. No significant difference was discovered in 3-year overall survival rate between GC patients with SEPT9 methylation and those without SEPT9 methylation. Combined detection could not improve the diagnostic value of GC, but could promote diagnosis sensitivity. In summary, the risk of PAX5 and SEPT9 gene methylation in GC patients presents higher when compared with healthy people. PAX5 gene methylation is closely related to age, while SEPT9 is closely related to tumor TNM stage, and PAX5 gene methylation can decrease the survival rate of GC patients. Detection of PAX5 gene methylation level can assist in evaluating the prognosis of GC patients.